Integration of Nile tilapia (Oreochromis niloticus) and vegetables (Amaranthus hybridus and Brassica rapa pekinensis) for improved production, water use efficiency and nutrient recycling. Issue 6 (17th October 2022) - Mulokozi, Deogratias Pius; Berg, Håkan; Tamatamah, Rashid Adam; Lundh, Torbjörn; Onyango, Paul Ochieng
Abstract: Sustainable agriculture intensification is an urgent challenge in developing countries including Tanzania. One potential solution is to adopt farming systems that increase farm production by optimizing resource use efficiency, and integrated aquaculture system, which involves farming of fish and crops, is an example of such systems. This study investigated the impact of Integrated agriculture and aquaculture (IAA) farming on water use efficiency, fish and vegetable production and overall system profitability, and how these parameters are affected by fish stocking densities. Oreochromis niloticus (2.5 g average initial weight) were cultured at low stocking density (five fish m −3, LSD), medium stocking density (eight fish m −3, MSD), and high stocking density (12 fish m −3, HSD) for 205 days. Brassica rapa pekinensis and Amaranthus hybridus cultivated adjacent to the fish tanks were irrigated with; (i) fish tank water, without any fertilizer inputs; (ii) fish tank water, partially fertilized; (iii) tap water, fully fertilized (farmers' practice); and (iv) tap water without any fertilizer inputs. Although the use of tank water from the high fish stocking density resulted in significantly higher vegetable yield, high fish stocking resulted in lower fish growth, profitability and water use efficiency compared to the other fish stocking densities, probably because of low survival rates (28%) at high stocking densities. The integration of fish at a medium stocking density with vegetables resulted in significantly higher net income than when fish and vegetables were grown separately. Abstract :